(untitled) (Teaching and Learning Inquiry, 2020)
This study describes students’ development of components of intercultural competence after completing a cultural diversity course and compared degrees of intercultural competence between a face-to-face course and an equivalent online section of the same course. Analysis of final written reflections from students demonstrated that students gained a deeper awareness of their lack of knowledge related to culture. The analysis also revealed that students in the online version of the course demonstrated higher degrees of intercultural openness and cultural self-awareness than did those in the face-to-face context. Findings from this study contribute significantly to the research on intercultural competence and the teaching of cultural diversity courses.